ANALISIS DAN KOMPARASI HADIS WANITA PEMBAWA SIAL - Fadhilah Is (SHAHIH (Jurnal Ilmu Kewahyuan), 2020)
Islam raises the degree of women accordance to nature and its role. Even in the Hadith is stated that women are the best jewelry in the world. However, orientalists, feminists, and misogynists are looking for loopholes to attack and corner Islam, especially regarding women. This is proven by many of the blessings that they spread with discussions wrapped in scientific studies and theology. However, all of it has been explicity denied both in the Koran, Hadith, and Studies of Islamic Scholars, and Experts. Among their Syuhat is Islam has made women unlucky, who have no role, and creatures that are hated and must be shunned. They argue with the authentic Hadith narrated in the Kutub as-Sittah